Motivasi Kinerja Pustakawan Universitas Atma Jaya Yogyakarta Setelah Keluarnya Jabatan Fungsional Pustakawan - Nugrohoadhi, Agung (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2014)
As the organizer of Universitas Atma Jaya Yogyakarta (UAJY), offering to UAJY’s librarians to get chance to switch profession from administrative to become librarian in which the candidate should of course be qualified by YSR. The objective of this conversion is to enhance library services. Librarian is not just about “book keepers” as many people defined, but its profession is expected to give proactive service to the end-users. FJP in UAJY has attracted librarians who have already been working in the library to re-consider on their profession. UAJY’s librarians demanded advanced services and reward based on what was signed in UU No. 43 Tahun 2007 tentang Perpustakaan.